Intra- and Interlaboratory Study of a Method for Testing the Antifungal Susceptibilities of Dermatophytes - Ghannoum, M. A. (American Society for Microbiology, 2004)
The National Committee for Clinical Laboratory Standards (NCCLS) M38-A standard for the susceptibility testing of conidium-forming filamentous fungi does not explicitly address the testing of dermatophytes. This multicenter study, involving six laboratories, investigated the MIC reproducibility of seven antifungal agents tested against 25 dermatophyte isolates (5 blinded pairs of five dermatophyte species per site for a total of 300 tests), using the method of dermatophyte testing developed at the Center for Medical Mycology, Cleveland, Ohio. The dermatophytes tested included Trichophyton rubrum, Trichophyton mentagrophytes, Trichophyton tonsurans, Epidermophyton floccosum, and Microsporum canis. Seven antifungals with activity against dermatophytes were tested, including ciclopirox, fluconazole, griseofulvin, itraconazole, posaconazole, terbinafine, and voriconazole. Interlaboratory MICs for all isolates were in 92 to 100% agreement at a visual endpoint reading of 50% inhibition as compared to the growth control and 88 to 99% agreement at a visual endpoint reading of 80% inhibition as compared to the growth control. Intralaboratory MICs between blinded pairs were in 97% agreement at a visual endpoint reading of 50% inhibition as compared to the growth control and 96% agreement at a visual endpoint reading of 80% inhibition as compared to the growth control. Data from this study support consideration of this method as an amendment to the NCCLS M38-A standard for the testing of dermatophytes.